PENGUATAN PENDIDIKAN KARAKTER SISWA MELALUI KOLABORASI ANTARA SEKOLAH DENGAN ORANG TUA DI SDIT AL JABAR GONDANG - Joko Riyanto; Sumarno (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to describe the strengthening of students’ character education through collaboration between the school and parents at SDIT Al Jabar Gondang. The study focuses on the concept of character education, forms of school–parent collaboration, communication patterns, synchronization of habituation at school and at home, and the supporting and inhibiting factors. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, teachers, parents, and students as data sources. The data were analyzed through data reduction, data display, conclusion drawing, and verification. The findings indicate that character education at SDIT Al Jabar Gondang is directed toward developing religious values, discipline, responsibility, independence, honesty, and social awareness. Collaboration is implemented through regular communication, parent meetings, parenting programs, liaison books, class communication groups, individual consultations, student development monitoring, and parental participation in school programs. The synchronization of habituation includes congregational prayer, Qur’an reading, time discipline, independent learning, cleanliness, politeness, and responsibility for assignments. Supporting factors include the school’s commitment, parental involvement, open communication, trust, and a shared educational vision. Meanwhile, inhibiting factors include parents’ limited time, differences in parenting styles, communication constraints, limited parental participation, and inconsistent habituation at home. Planned, open, and continuous collaboration creates continuity in character education between school and family environments.